Investing in PNB product customer awareness toward Amanah Saham Malaysia / Norazwan Nordin - Nordin, Norazwan (Faculty of Business and Management, 2009)
Mutual fund or better known as unit trust fund in Malaysia is an investment vehicle created by asset management companies specializing in pooling saving from both retail and institutional investor. Individual investors seeking liquidity, portfolio diversification and investment expertise are increasing closing unit trust funds as their investment vehicle. However, this investor does differ in their preferences based on their risk threshold liquidity needs and their needs to comply with religious requirement. One of the Permodalan Nasional Berhad (PNB) product which is Amanah Saham Malaysia (ASM). Amanah Saham Malaysia has been launched 20 April 2000. ASM scheme is very synonym with PNB because the product has launched at Minggu Saham Amanah 2000 Putra World Trade Centre in Kuala Lumpur. Base on product, the purpose of this research to identify customer awareness and motivation factors toward Amanah Saham Malaysia. For this research, will be use descriptive study because researcher uses primary data such as questionnaire to identify level of customer awareness toward ASM. The questionnaire will be close-ended question and structured design which used dichotomous question and Likert scale. Secondary data will be used such as journal, articles, newspaper, report and Master Prospectus from ASNB.